Revision of the first Carboniferous palaeofloristic locality discovered in Argentina - Correa, Gustavo Alejandro (2019)
The first Carboniferous palaeofloristic locality recognized in Argentina is situated to the south of the Sierra Chica de Zonda in San Juan Province, Argentina. The fossiliferous site known as Retamito or Río del Agua provided plant remains which were studied by the Polish scientist Ladislaus Szajnocha in 1891. Szajnocha proposed an early Carboniferous age for the assemblage and described some species of lycophytes and sphenophytes, and foliage of cordaitalean and probable pteridosperms. Subsequent studies of this outcrop and its palaeontological content have been few, and a new interdisciplinary approach is needed. The succession is interpreted as fluvial-deltaic in origin, with intercalation of shallow marine deposits, which provided diagnostic plant components of the Nothorhacopteris/Botrychiopsis/Ginkgophyllum Biozone of the late Carboniferous in Argentina. Palynological assemblages recovered from the same strata contain bisaccate taeniate pollen and spores (e.g. Striatosporites heyleri) that support an age probably not older than early Moscovian.